Implementation of Lunar Celestial Reference System (LCRS) for Practical Use and Interoperability - Elrod, M. K. (2025)
With the standardization of an inertial lunar reference system, the Lunar Celestial Reference System (LCRS) and the accompanying Lunar Coordinate Time TCL) it becomes an important next step to consider the practical applications and use of LCRS. LCRS and the accompanying necessary, but not yet standardized, body-fixed lunar reference system (LRS) that enable operations on and near the surface of the Moon, require interoperability with Earth reference systems. TCL is a coordinate time centered on the Moon analogous to Geocentric Coordinate Time (TCG). Currently there is not a connection between practical times like Barycentric Dynamic Time (TDB), or UTC, or a defined lunar surface time analogous to TT and UTC. Computations using LCRS and TCL remain in the theoretical realm until they can be tied to measured time scales. Current practice for computing position and motion using coordinate systems around the Moon use TDB as a default to connect to UTC for spacecraft and observations that move from Earth to the Moon. Furthermore, current calculations of the lunar orientation angles between LCRS and LRS for body-fixed systems like Mean Earth (ME) and Principal Axis (PA) also use TDB as this is dependent on the rotation rate of the Moon. The practical use of LCRS is to create tracking capabilities, define a lunar-oriented position to find celestial objects and to support a lunar-based navigation system. While many missions have successfully traveled from the Earth to the Moon prior to the adoption of the LCRS, more and more missions are being planned and a standardized coordinated system and time for all the missions to use is becoming necessary. Since missions are initially launched from Earth and then transition to the lunar sphere of influence it is critical to: a) have a defined practical time for LCRS either by determining ing the relationship between TCL and TDB or UTC/TT, or defining a local lunar surface time (e.g. Lunar Time TL or LTC etc.) that can be defined by a real or measured time and/or has some connection to terrestrial time; b) determine a crossover point between the sphere of influence of Earth and the Moon, and c) determine the relationship between LCRS and the body fixed system LRS. With all this in place it is possible to have a standardized system of navigation for the surface and lunar orbit, the ability to track celestial references like navigation stars and planets, and the data necessary to create a lunar navigation system. We will illustrate practical uses for the LCRS, ensuring they are consistent with IAU standards and interoperable with other reference systems. Such uses could include navigation for locations on the surface of the moon using celestial objects (stars and planets), precise coordinates (of stars and planets) in LCRS, and transformation parameters from LCRS to LRS.